The Emotional Intelligence of Paediatric Residents – A Descriptive Cross-Sectional Study. (1st June 2016) - McLeod, S; Sonnenberg, L
Abstract: BACKGROUND: Emotional Intelligence (EI) is a type of social intelligence with high scores achieved through factors including being empa-thetic in interpersonal relationships, displaying flexibility in adapting to change, and managing stressful situations. There has been an explosion of research into EI in medicine since many of the social competencies described may have a direct impact on patient care. OBJECTIVES: The objective of this study was to describe EI of pediatric residents and to identify if there are EI skills that should be selected for targeted intervention in this population. DESIGN/METHODS: This was a cross-sectional study administering the EQi-2.0 © psychometric instrument to all pediatric residents at a Canadian residency program. Scores were analyzed by year of training, gender, and age. RESULTS: Thirty-five residents completed the EQi-2.0 © (100% response rate). Their overall EI score was not significantly different than a normative group of college educated professionals. There was no correlation between overall EI and year of training, gender, or age. Residents had relative strengths in the subcategories Emotional expression, Interpersonal Relationships, Empathy, and Impulse Control (all p<0.05). Areas of relative weakness were in the subcategories Stress Tolerance, Assertiveness, Independence and Problem Solving (all p<0.05). There were significantly higher scores in the subcategories Independence, and Problem Solving for residents over thirty years old when compared to younger residents (both p<0.05). CONCLUSION: The EI of pediatric residents is consistent with that of other professionals. Educational interventions may be useful in the areas of weakness, however, individual score reports vary so emphasizing the individual learning needs of each resident based on their weaknesses may be the best educational intervention to enhance the physician-patient relationship.